Spatial Modeling of Agricultural Carbon Footprints: Assessing Greenhouse Gas Emissions Based on Livestock Population and National NPK Fertilizer Consumption - Saida; Pieter J. Kunu; Andi Apriany Fatmawaty (Agriculture Journal, 2026)
This study addresses the critical challenge of balancing national food security with climate mitigation by developing a spatial model of Indonesia's agricultural carbon footprint. Amid global Net Zero Emissions efforts, it identifies geographical "hotspots" of non- CO2 greenhouse gases using secondary data from the Ministry of Agriculture and PT Pupuk Indonesia (2020–2024). Applying the Intergovernmental Panel on Climate Change IPCC Tier 1 methodology, this study estimates methane (CH4) emissions from livestock enteric fermentation and nitrous oxide (N2O) emissions from NPK fertilizer consumption. GIS-based spatial analysis reveals significant clustering patterns, with East Java contributing 26.54% of national livestock methane emissions based on 2023 livestock population data. While methane dominates in total emission volume, N2O emissions from NPK fertilizer application demonstrate higher atmospheric persistence and global warming potential. Statistical analysis indicates that fertilizer management explains 78% of the variance in soil emissions (np2 = .78), confirming that nutrient input is a primary determinant of soil-based carbon flux variability. These findings are supported by spatial autocorrelation results and provincial emission estimates, which identify major emission clusters along Java Island and South Sulawesi agricultural corridors, highlighting the need for region-specific mitigation strategies.